ANTI-ACNE FACIAL WASH FORMULATION FROM RED BETEL LEAF EXTRACT (PIPER CROCATUM RUIZ & PAV) - Hindun, Siti; Gazzali, Amirah Mohd; Najihudin, Aji; Hamdani, Siva; Rantika, Nopi; Azizah, Winanda Nur (Jurnal Ilmiah Farmako Bahari, 2024)
Acne can be caused by dust, sweat, and dirt that stick to the skin, forming blackheads. When blackheads become infected with bacteria, inflammation can occur. Therefore, it is essential to maintain good skin hygiene. One way to do this is by using natural ingredients with antibacterial properties. Red betel leaf is known to have antibacterial activity. This study aims to create a facial wash using red betel leaf extract that exhibits antibacterial properties against Propionibacterium acnes. The red betel leaf was extracted using the maceration method. Antibacterial testing was conducted against Propionibacterium acnes bacteria using the suitable diffusion method with a combination of red betel leaf extract at 10%, 15%, and 20%. The study found that facial wash products containing extract concentrations of 10%, 15%, and 20% demonstrated good physical stability, meeting the requirements of SNI-19-4380-1996 for pH, viscosity, specific gravity, and foam height. Additionally, the products showed potent antibacterial activity against Propionibacterium acnes bacteria, with inhibition zones of 29.0 mm, 32.6 mm, and 35.3 mm for the 10%, 15%, and 20% concentrations, respectively.